Slavica 2021: 60 Years, 50 Issues - Agyagási, Klára (Slavica, 2021)
The article gives an overview of the process, by which Slavica, the periodical of the University of Debrecen and its institutional predeccesors has developed from a local publication into a periodical of national and even international significance. The historical overview of the past 60 years highlights those changes that have occured in the profile of the periodical compared to the initial objectives, commemorates the outstanding perspective-minded heads of previous editorial committees, points out situations, when serious decisions had to be taken, in which a special balance of compulsion and neccessity brought the solution, which looking back from the future, moved the periodical forward. The article is concluded by enumerating the benefits offered by the online format and by formulating new objectives